(untitled) (Geo-Eco-Marina, 2020)
Among the 26 nature reserves established in the Transylvanian Basin, 13 have the status of geological reserves, and four of them are represented by mud volcanoes. Active volcanoes currently occur only in the area of Băile Homorod. The other three reserves, Filiaş, Monor and Hăşag, represent mud volcanoes in their late stage of development. Assessment of these four reserves indicate that they show scientific importance, but only those from Homorod present interesting feature of active mud volcanoes as well as a high scientific value. Educational and touristic values of the three reserves with inactive mud volcanoes are rather limited, especially that they are remotely situated and they are more difficult to find, as there are no signs for location or explanatory panels. Also, the risk of degradation of the three inactive mud volcano fields are greater, due to cessation of their activity, possibly caused by exhaustion of gases generating them, or drying of the groundwater level crossed by the gases in their way to the surface.